2017
DOI: 10.1002/mp.12527
|View full text |Cite
|
Sign up to set email alerts
|

Risk assessment of a new acceptance testing procedure for conventional linear accelerators

Abstract: Potential errors due to human factors were decreased for the ATP compared to ATP so it is possible that a largely automated linac ATP can mitigate many error occurrences. Manufacturers should be careful when designing an EPID-based ATP to address errors in the EPID pixel sensitivity map which can potentially lead to a significant impact on patients' treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 19 publications
1
3
0
1
Order By: Relevance
“…This observation agrees well with other studies reported in the literature that demonstrate that automating the ATC process and using standard beam data reduces the probability of occurrence of errors . A comparison of using manufacturer‐supplied phantom and automation (with EPID) vs conventional techniques with tools that are not an integral part of the linac has shown that use of manufacturer‐supplied phantoms and automation reduces the number of FMs by slightly more than half, from 556 FMs to 255 FMs, for a c‐arm linac …”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…This observation agrees well with other studies reported in the literature that demonstrate that automating the ATC process and using standard beam data reduces the probability of occurrence of errors . A comparison of using manufacturer‐supplied phantom and automation (with EPID) vs conventional techniques with tools that are not an integral part of the linac has shown that use of manufacturer‐supplied phantoms and automation reduces the number of FMs by slightly more than half, from 556 FMs to 255 FMs, for a c‐arm linac …”
Section: Discussionsupporting
confidence: 90%
“…17,18 A comparison of using manufacturer-supplied phantom and automation (with EPID) vs conventional techniques with tools that are not an integral part of the linac has shown that use of manufacturer-supplied phantoms and automation reduces the number of FMs by slightly more than half, from 556 FMs to 255 FMs, for a c-arm linac. 5 In the conventional approach of measurements of output in a c-arm linac, a reference detector is typically placed between the linac head and a water tank. However, due to the space limitation of the ring-gantry linac, the reference detector could not be positioned on the water tank and it was instead attached to the bore cover with a tape (Fig.…”
Section: Rankmentioning
confidence: 99%
See 2 more Smart Citations
“…Uma das ferramentas de análise de risco elencadas no TG-100 é a Failure Modes and Effects Analysis (FMEA), já amplamente utilizada na indústria e na engenharia. Atualmente, em um serviço de radioterapia, é possível aplicar esta metodologia a diferentes equipamentos, não só os contemplados no SEVRRA, além da ampla possibilidade de uso desta análise em diferentes técnicas de tratamento, processos e até mesmo em procedimentos de controle de qualidade [9], [10], [11].…”
Section: Introductionunclassified